Multimodal interaction for science learning in preschool: Conceptual development with external tools across a science project. Issue 3 (3rd July 2019) - Samuelsson, Robin
ABSTRACT: This paper studies the scaffolding of conceptual development for children aged 4–5 years old during a science project at a Swedish preschool. It specifically examines how bodily knowledge and language are used in interaction, and how conceptual knowledge can be scaffolded with the use of external tools and artefacts. The science project was tracked for seven weeks and the analytical focus is on situations where a computer and a projected screen are used. The study shows how interactions afforded by the set-up provide a virtual-physical setting where teachers and children can interact using both language and bodily modes. As such, it provided an interactional space where teachers can scaffold children's tactile understandings towards conceptual knowledge by building on the children's prior experiences, and knowledge is cumulated over time during the project. This is accomplished by focusing attention on the topic and through the use of tools in interaction. Possible implications and uses for early childhood education are discussed in the light of these results.